2021
DOI: 10.1002/alr.22799
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal and gastrointestinal bacterial composition and abundance are stable after 1 week of once‐daily oral antibiotic treatment for chronic rhinosinusitis

Abstract: Background: Despite the widespread prescription of antibiotics for the treatment of chronic rhinosinusitis (CRS), their efficacy remains uncertain. Limited penetration of systemic antibiotics into the sinonasal mucosa has been reported previously by this group. This study aimed to investigate the short-term effects of antibiotics on the sinus and gut microbiota as well as any relationships these had with drug distribution.Methods: Thirty subjects undergoing functional endoscopic sinus surgery for CRS were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 70 publications
(117 reference statements)
0
28
0
Order By: Relevance
“…Eleven articles within the category of antibiotics only were utilized in the creation of the antibiotic section of this systematic review [4,[17][18][19][20][21][22][23][24][25][26]. Eight of the eleven selected clinical trials used some sort of randomization [4,17,19,21,22,[24][25][26], with only three being placebo-controlled [4,21,25] or blinded [21,25,26]. Total sample size ranged from 5 [20] to 103 [25] participants, whereas group sample size ranged from 3 [17] to 37 [25].…”
Section: Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven articles within the category of antibiotics only were utilized in the creation of the antibiotic section of this systematic review [4,[17][18][19][20][21][22][23][24][25][26]. Eight of the eleven selected clinical trials used some sort of randomization [4,17,19,21,22,[24][25][26], with only three being placebo-controlled [4,21,25] or blinded [21,25,26]. Total sample size ranged from 5 [20] to 103 [25] participants, whereas group sample size ranged from 3 [17] to 37 [25].…”
Section: Antibioticsmentioning
confidence: 99%
“…The most common utilized were vancomycin [17,18,21,23], ciprofloxacin [17,18,23], metronidazole [17,18,23] and amoxicillin [4,21,24]. The length of intervention ranged from 3 [19] to 14 [25] days, with six of the studies including a 7 day intervention period [17,18,21,23,24,26]. The reasons for prescription mainly consisted of research purposes [4,[17][18][19][20][21][22].…”
Section: Antibioticsmentioning
confidence: 99%
“…Using amoxicillin-clavulanate for patients with acute exacerbation of CRS did not change the clinical course of this disease [ 88 ]. It has been suggested that short-term oral antibiotics poorly penetrate SM [ 89 ].…”
Section: Conventional Treatment Approachesmentioning
confidence: 99%
“…Maniakas et al 7 conducted a double-blind, randomized trial demonstrating that low-dose oral azithromycin aids polyp resolution in patients with persistent polyposis despite ESS and high-volume corticosteroid irrigations. Siu et al 8 performed a randomized study of 30 patients undergoing ESS and analyzed sinonasal and stool samples using RNA sequencing. After randomization to doxycycline, roxithromycin, or no antibiotic (control), there were no significant bacterial shifts or changes in diversity or load.…”
Section: Chronic Rhinosinusitismentioning
confidence: 99%
“…conducted a double‐blind, randomized trial demonstrating that low‐dose oral azithromycin aids polyp resolution in patients with persistent polyposis despite ESS and high‐volume corticosteroid irrigations. Siu et al 8 . performed a randomized study of 30 patients undergoing ESS and analyzed sinonasal and stool samples using RNA sequencing.…”
Section: Chronic Rhinosinusitismentioning
confidence: 99%